MOFs for Electrocatalysis: From Serendipity to Design Strategies - Aiyappa, Harshitha Barike; Masa, Justus; Andronescu, Corina (Small Methods, 2019)
The rapid upsurge of metal–organic frameworks (MOFs) as well as MOF-derived materials has stimulated profound interest to capitalize on their many potential untapped benefits in electrocatalysis for energy applications. The possibility of tuning the metal–ligand junctions of the MOF architecture opens new avenues to design robust, extended heterostructures for addressing the present-day energy challenges. Interestingly, despite having detailed crystallographic information, it is often difficult to envisage the interplay of charge transport (electrons and ions), mass transport (pore system) together with the specific effects of the molecularly defined reaction center of MOFs for a given electrocatalytic reaction. Here, guidelines are offered for judiciously engineering the electronic structure of MOFs to deliver targeted electrocatalytic function. Some of the pivotal works on MOF-based materials for electrocatalysis are discussed, which can be correlated to the biological models in terms of their structural resemblance and an instructive insight is provided about the “new chemistry” that can be explored based on the lessons learned from nature in combination with the theoretical understanding of the energetics of the reactions.